2008
DOI: 10.1108/09684880810868457
|View full text |Cite
|
Sign up to set email alerts
|

The impact of quality assurance measures on student services at the Japanese and Thai private universities

Abstract: PurposeThe purpose of the paper is to ascertain students' perceptions on quality of services provided by private universities in Thailand and Japan and how these affected decisions selecting a university. A comparative study aims to focus on how cultural and economic factors affected their decisions.Design/methodology/approachResearch design sought students' perceptions through empirical surveys on the type of factors which influenced their decisions in selecting a university. As the students needed to form th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 22 publications
5
40
0
Order By: Relevance
“…Another study supported that effective institution counseling support service was bound to be one important factor in helping student academic success [8]. This study also demonstrated that this is the third most important factor that influences student satisfaction.…”
Section: Part 4: Cross Tabulation Analysis Between Public and Privatesupporting
confidence: 51%
See 4 more Smart Citations
“…Another study supported that effective institution counseling support service was bound to be one important factor in helping student academic success [8]. This study also demonstrated that this is the third most important factor that influences student satisfaction.…”
Section: Part 4: Cross Tabulation Analysis Between Public and Privatesupporting
confidence: 51%
“…It can be determined by looking at the financial assistance given to the students; the expenses needed during the time of study, the tuition fee payment plan, the scholarship offered, extra income from part-time job, and so on. The finding of [8] indicated that the financial assistance and tuition fees were the second most important factor that influenced the students' satisfaction.…”
Section: Part 4: Cross Tabulation Analysis Between Public and Privatementioning
confidence: 95%
See 3 more Smart Citations